Analysis of the Development of Cyber Crime in Indonesia - Dijan Widijowati (Universitas Dharma Wacana, 2022)
The development of information and communication technology has both positive and negative impacts. Advances in information technology and technology can also be used by perpetrators of criminal acts (cyber) in completing their evil intentions so that today to commit crimes between countries, the perpetrator of a crime does not have to be present in a particular country, but he can do it still by being in his country even in his bedroom. This study aims to analyze the development of Cyber Crime crimes in Indonesia. The research method used by the author is a normative research method with a descriptive model that explores aspects of legal regulations related to cybercrime so that the results of the author's research are expected to provide a minimum contribution for parties who wish to explore cyber law issues in Indonesia. The research results show that the development of computer crime is now not limited to illegal access. Still, the development of the scope of crimes and cyber crimes has entered the realm of computer security systems and even entered business activities in cyberspace, known as e-commerce fraud, tax, and stock exchange fraud to intellectual property right fraud. Apart from determining the type of prison sentence for perpetrators of cyber crimes, alternatives such as social work punishment and supervision punishment can also be found.